Accuracy of Digital Radiography and Cone Beam Computed Tomography on Periapical Radiolucency Detection in Endodontically Treated Teeth - Tadas Venskutonis; Povilas Daugela; Marijus Strazdas; Gintaras Juodzbalys (Stilus Optimus, 2014)
Objectives: The aim of the present study was to compare the accuracy of intraoral digital periapical radiography and cone beam computed tomography in the detection of periapical radiolucencies in endodontically treated teeth. Material and Methods: Radiographic images (cone beam computed tomography [CBCT] scans and digital periapical radiography [PR] images) from 60 patients, achieved from September 2008 to July 2013, were retrieved from databases of the Department of Oral Diseases, Lithuanian University of Health Sciences. Twenty patients met inclusion criteria and were selected for further evaluation. Results: In 20 patients (42.4 [SD 12.1] years, 65% men and 35% women) a total of 35 endodontically treated teeth (1.75 [SD 0.91]; 27 in maxilla and 8 in mandible) were evaluated. Overall, it was observed a statistical significant difference between the number of periapical lesions observed in the CBCT (n = 42) and radiographic (n = 24) examinations (P < 0.05). In molar teeth, CBCT identify a significantly higher amount of periapical lesions than with the radiographic method (P < 0.05). There were significant differences between CBCT and PR in the mean number of lesions identified per tooth (1.2 vs 0.66, P = 0.03), number of teeth with lesions (0.71 vs 0.46, P = 0.03) and number of lesions identified per canal (0.57 vs 0.33, P = 0.005). Considering CBCT as "gold standard" in lesion detection with the sensitivity, specificity and accuracy considering as score 1, then the same parameters of PR were 0.57, 1 and 0.76 respectively. Conclusions: Within the limitations of the present study, it can be concluded that cone beam computed tomography scans were more accurate compared to digital periapical radiographs for detecting periapical radiolucencies in endodontically treated teeth. The difference was more pronounced in molar teeth.